Callous-unemotional traits moderate anticipated guilt and wrongness judgments to everyday moral transgressions in adolescents - Vasconcelos, Margarida Fátima Gomes (2021)
The Supplementary Material for this article can be found online at: https://www.frontiersin.org/articles/10.3389/fpsyt.2021.625328/full#supplementary-material